2018
DOI: 10.1093/ijpor/edy025
|View full text |Cite
|
Sign up to set email alerts
|

Is Facebook Eroding the Public Agenda? Evidence From Survey and Web-Tracking Data

Abstract: Preserving a common public agenda positively affects social integration, minimizing social cleavages and polarization. While social media are known for fragmenting the media environment, research has not devoted much attention to their effect on the public agenda. This paper addresses whether consuming news through Facebook shapes individual agendas that diverge from the set of most important problems (MIPs) as perceived by the general public. Our research design combines survey and web-tracking data to analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 45 publications
0
18
0
2
Order By: Relevance
“…Research has shown that the topic of news is of relevance in reaching an audience through Facebook, for instance, soft news was preferred over hard news in one examination (Bakshy et al, 2015). Second, not all individuals that use a social media channel will be presented with the same agenda in their news feed on Facebook (Cardenal et al, 2018). This might lead to more fragmented audiences, especially when compared with legacy media (Feezell, 2018).…”
Section: Agenda-setting Through Social Mediamentioning
confidence: 99%
“…Research has shown that the topic of news is of relevance in reaching an audience through Facebook, for instance, soft news was preferred over hard news in one examination (Bakshy et al, 2015). Second, not all individuals that use a social media channel will be presented with the same agenda in their news feed on Facebook (Cardenal et al, 2018). This might lead to more fragmented audiences, especially when compared with legacy media (Feezell, 2018).…”
Section: Agenda-setting Through Social Mediamentioning
confidence: 99%
“…Reliance on specific sources may affect issue horizon wideness and compatibility by itself. However, theoretical arguments and empirical findings suggest that individuals with extreme political attitudes will be much more vulnerable to such effects (Bruns 2019).…”
Section: Information Environments Attitude Extremity and Issue Horizonsmentioning
confidence: 99%
“…An extreme version of this scenario-highly individualized, isolated information environments, disconnected from the outside world-has been described with the popular filter bubble metaphor (Pariser 2011). Research has debunked this extreme scenario (Bruns 2019;Haim et al 2018;Hindman 2012;Mahrt 2020;Möller et al 2018;Zuiderveen Borgesius et al 2016); if any, filter bubbles must be regarded a "fringe" phenomenon that is likely to occur only under specific conditions. Thus, algorithmic content curation will usually not lead to completely different, individualized issue sets.…”
Section: Social Media Reliance and Issue Horizonsmentioning
confidence: 99%
See 1 more Smart Citation
“…That study, however, did not focus on the access of news through social media, which is an increasingly common way of accessing news, and the main way of accessing digital news in Colombia. A study analyzing how agenda setting occurs within a networked, social media environment in Spain found that consuming news through Facebook influence individual in how they prioritize issues, but that those individual's perception of important issues was different than what the general public deemed important (Cardenal et al 2019). Similarly, Tremayne (2017) tested for the competing theories of agendas in a networked environment, that of fragmentation versus homogeneity and found support for homogeneity between traditional news media agenda and news media agenda shared on Facebook.…”
Section: Consensus Building In a Digital Environmentmentioning
confidence: 99%